Instilling Moral Values in Islamic Religious Education Learning Facing the Millennial Era at SMP Negeri 1 Sungai Limau - Marfiyanti; Mita Muhaisyah; Giva Yulnefsi; Netra Sovia; Syafrina Yulia (CV Edujavare Publishing, 2026)
This study aims to analyze the implementation of moral values ​​cultivation in Islamic Religious Education (IRE) learning and identify the challenges and strategies of IRE teachers in responding to the millennial era at SMP Negeri 1 Sungai Limau. The rapid development of digital technology has influenced students' behavior, requiring adaptive and character-oriented Islamic education. This research employed a qualitative descriptive approach. The research subjects consisted of Islamic Religious Education teachers, students, and school administrators. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings indicate that the cultivation of moral values ​​in IRE learning is carried out through teacher role modeling, habituation of religious activities, integration of moral values ​​into learning materials, and the wise use of digital media. The main challenges include the influence of social media, low self-control among students, and shifts in social interaction patterns. Teachers address these challenges through persuasive approaches, strengthening character education, and collaboration between schools and parents.